Disturbance-induced reduction of biomass carbon sinks of China's forests in recent years. (20th November 2015) - Zhang, Chunhua; Ju, Weimin; Chen, Jing M; Wang, Xiqun; Yang, Lin; Zheng, Guang
Abstract: Forests play a critical role in mitigating climate change because of their high carbon storage and productivity. China has experienced a pronounced increase in forest area resulting from afforestation and reforestation activities since the 1970s. However, few comprehensive analyses have been made to assess the recent dynamics of biomass carbon sinks in China's forests. This study refined biomass carbon sinks of China's forests based on eight forest inventories from 1973 to 2013. These sinks increased from 25.0 to 166.5 Tg C yr −1 between 1973 and 2008, and then decreased to 130.9 Tg C yr −1 for the period of 2009–2013 because the increases in forest area and biomass carbon density became slower. About 7% and 93% of this sink reduction occurred in planted and natural forests. The carbon sinks for young, middle-aged and premature forests decreased by 27.3, 27.0, and 7.6 Tg C yr −1, respectively. 42% of this decrease was offset by mature and overmature forests. During 2009–2013, forest biomass carbon sinks decreased in all regions but the north and northwest regions. The drivers for changes of forest biomass sinks differ spatially. More intensive harvest of young and middle-aged forests and snow damage were the major drivers for the decreases of biomass carbon sinks in the east (8.0 Tg C yr −1 ) and south (19.8 Tg C yr −1 ) regions. The carbon sink reduction in the southwest region (16.7 Tg C yr −1 ) was mainly caused by increased timber harvesting and natural disturbances, such as droughts in Yunnan province, snow damage in Guizhou province and forest fires in Sichuan province. In the northeast region, the sink reduction occurred mainly in Heilongjiang province (7.9 Tg C yr −1 ) and was caused dominantly by the combined effects of diseases, windthrow and droughts. The carbon sink increase was primarily attributed to forest growth and decreased deforestation in the north (10.0 Tg C yr −1 ) and northwest (2.3 Tg C yr −1 ) regions.